9x+6-2x+10=4x+1

Simple and best practice solution for 9x+6-2x+10=4x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+6-2x+10=4x+1 equation:



9x+6-2x+10=4x+1
We move all terms to the left:
9x+6-2x+10-(4x+1)=0
We add all the numbers together, and all the variables
7x-(4x+1)+16=0
We get rid of parentheses
7x-4x-1+16=0
We add all the numbers together, and all the variables
3x+15=0
We move all terms containing x to the left, all other terms to the right
3x=-15
x=-15/3
x=-5

See similar equations:

| 1=10y-9 | | 9+3x=3(x+3) | | -2-18-8j=-2(4j+10) | | 9(x-8)=5x+64+2x+88 | | 4(g+1)=20 | | 2(-x+4)=6(2x-1) | | (-1.5x)+12=2.5x-12 | | 20g=9(2g-4)-4 | | -9=1/2k | | 3+7x=15+5x= | | -3f+7(-f+1)=7-10f | | X+2x-4-x=2x+4 | | 16=4t-2t | | 10x-3=(-5x)-18 | | 12r-4=-2(-6r+2) | | 7x+24+3x-48=2x+80+4x+72 | | 8x^2-4=6 | | -6b+7=7b+1-13b | | 1=q/2 | | 2x+8=-x+14 | | 9(h-1)=-9+9h | | (-7x)+14=4x-19 | | 9x+x14=2(5x+7) | | -13k-11=20-7k+17 | | x5-11=14 | | .5=q+0.6666 | | 20c-11=2(10c-19) | | 5x+8=× | | 2x+20=(-3x)-25 | | -6=x4-9 | | -2j=2(-j+3) | | s/5+12=13 |

Equations solver categories